Organizational Transformation : How to Achieve It, One Person at a Time - Avolio, Bruce J. (Stanford, CA : Stanford University Press, 2020)
It is estimated that approximately seventy percent of organizations fail in their attempts to implement transformative change. This book will help lessen that rate. Using real-world examples, Bruce J. Avolio maps four states of change that any organization must go through: identifying and recognizing, initiating, emerging and impending, and institutionalizing new ways of operating. Each state is described in detail, as are the leadership qualities necessary to solidify and transition from one to the next. These "in-between moments" are an often-overlooked key to organizational transformation. So too is the fact that organizational change happens one individual at a time. For transformation to take root, each person must shift his or her sense of self at work and the role that he or she plays in the transforming organization. Intended as a road map, rather than a "how-to" manual with fixed procedures, Organizational Transformation will help leaders to locate their organization's position on a continuum of progress and confidently navigate planned, whole-systems change, overcoming the challenges of growing from and adjusting to watershed moments.
Frontmatter -- Contents -- Acknowledgments -- Preamble -- 1. Building the narrative -- 2. First principle: changing the self-concept -- 3. The four-state model -- 4. The identifying state: the signal for change -- 5. The initiating state: beginning the launch -- 6. The impending state: breaking better -- 7. The institutionalizing state: defining “my organization” -- 8. A tale of two transformations -- 9. Becoming the change and sustaining it -- 10. Developing as a transformative leader -- Notes -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 15. Sep 2020)
Keywords: Organizational change -- Management; identity; leadership; leadership development; organizational change; ownership; self-concept.; states; transformation; BUSINESS & ECONOMICS / Organizational Behavior